2013
DOI: 10.1371/journal.pone.0074214
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Related to Emergency Department Care: A Systematic Review

Abstract: ObjectiveTo systematically review the literature regarding the prevalence, preventability, severity and types of adverse events (AE) in the Emergency Department (ED).MethodsWe systematically searched major bibliographic databases, relevant journals and conference proceedings, and completed reference reviews of primary articles. Observational studies (cohort and case-control), quasi-experimental (e.g. before/after) studies and randomized controlled trials, were considered for inclusion if they examined a broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 31 publications
(145 reference statements)
3
79
0
4
Order By: Relevance
“…Therefore, mild reactions such as nausea or dizziness are underrepresented in this data set. However, our adverse drug event rate of 0.31% was similar to that of other studies conducted in the ED, which range from 0.16% to 6.0%, 31 suggesting that we captured the majority of clinically significant adverse drug events. The external validity of this study is limited by heterogeneity across computerized provider order entry and clinical decision support systems.…”
Section: Limitationssupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, mild reactions such as nausea or dizziness are underrepresented in this data set. However, our adverse drug event rate of 0.31% was similar to that of other studies conducted in the ED, which range from 0.16% to 6.0%, 31 suggesting that we captured the majority of clinically significant adverse drug events. The external validity of this study is limited by heterogeneity across computerized provider order entry and clinical decision support systems.…”
Section: Limitationssupporting
confidence: 82%
“…According to previous research, adverse drug event occurrence ranges from 0.16% to 6.0% in the ED. 31 Using this range, 5,000 chart reviews were expected to capture between 6 and 300 adverse drug events, resulting in a manageable number of chart reviews across all days of the week while maintaining enough volume to capture adverse drug events. In adherence with the Health Insurance Portability and Accountability Act (HIPAA) regulations and local institutional review board requirements, all ED visits for patients aged 18 to 89 years were included.…”
Section: Methodsmentioning
confidence: 99%
“…Anderson et al showed an overall incidence of error at 0.13% in ED care 6. Overall, there is a dearth of high-quality evidence describing the incidence of error and adverse events in the ED 10. The Anderson study, reviewing only physician complaints about ED patient care, found that 22.6% of the errors identified were identified by complaints and 19.9% of adverse events were identified by complaints, although the proportion that were preventable was not reported 6…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggest that up to 10% of patients admitted to ED experience medication errors during their ED stay. Even 70% of these mistakes could have been prevented 7 8…”
Section: Introductionmentioning
confidence: 99%